Feminist Experiences of 'Studying Up': Encounters with International Institutions. (January 2019) - Holmes, Georgina; Wright, Katharine A. M.; Basu, Soumita; Hurley, Matthew; Martin de Almagro, Maria; Guerrina, Roberta; Cheng, Christine
This article makes the case for feminist IR to build knowledge of international institutions. It emerges from a roundtable titled 'Challenges and Opportunities for Feminist IR: Researching Gendered Institutions' which took place at the International Studies Association Annual Convention in Baltimore in 2017. Here, we engage in self-reflexivity, drawing on our conversation to consider what it means for feminist scholars to 'study up'. We argue that feminist IR conceptions of narratives and the everyday make a valuable contribution to feminist institutionalist understandings of the formal and informal. We also draw attention to the value of postcolonial approaches and multi-site analyses of international institutions for creating a counter-narrative to hegemonic accounts emerging from both the institutions themselves, and scholars studying them without a critical feminist perspective. In so doing, we draw attention to the salience of considering not just what we study as feminist International Relations scholars but how we study it.